A method to protect Cuckoo filters from soft errors. (May 2017) - Reviriego, P.; Pontarelli, S.; Maestro, J.A.
Abstract: Soft errors that corrupt the value of bits stored in registers or memories are a major issue for modern electronic systems. To ensure that they do not cause failures, error detection and correction codes are commonly used to protect memories. When memories are used for a specific application, sometimes it is possible to optimize the protection based on the knowledge of the application. One example is the memories used in network devices for packet processing. In particular, the protection of approximate membership check structures such as Bloom filters has been recently studied showing that it is possible to optimize the protection. Cuckoo filters are an alternative to Bloom filters for approximate membership check that has been recently proposed. Cuckoo filters are interesting as they are competitive in terms of memory usage for low false positive rates and also support the removal of elements. In this paper, the protection of Cuckoo filters against soft errors is studied showing that it can be enhanced by exploiting its structure and using the knowledge of the effects on an error in a Cuckoo filter.